2008
DOI: 10.1016/j.combustflame.2008.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Three-stage autoignition of gasoline in an HCCI engine: An experimental and chemical kinetic modeling investigation

Abstract: The alternative HCCI combustion mode presents a possible means for decreasing the pollution with respect to the conventional gasoline or diesel engines, while maintaining the efficiency of a diesel engine or even increasing it. This paper investigates the possibility of using gasoline in an HCCI engine and analyses the auto-ignition of gasoline in such an engine. The compression ratio that has been used is 13.5, keeping the inlet temperature at 70 °C, varying the equivalence ratio from 0.3 to 0.54 and the EGR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 29 publications
(25 reference statements)
2
27
0
Order By: Relevance
“…Although the pure gasoline contains relatively small amount of long straight molecules (n-heptane), its pressure trace still features a two-stage increase, which agrees with previous researches [11]. Machrafi and Cavadias [12]. found that the homogenous charge compression ignition combustion has three heat release stages: they are the cool flame reactions by long straight molecules such as n-heptane, the obstructed preignition by the formation of benzyl radical from aromatics such as toluene, and the main heat release stage [12].…”
Section: Effect Of Fuel Composition On Ignition Processsupporting
confidence: 87%
See 1 more Smart Citation
“…Although the pure gasoline contains relatively small amount of long straight molecules (n-heptane), its pressure trace still features a two-stage increase, which agrees with previous researches [11]. Machrafi and Cavadias [12]. found that the homogenous charge compression ignition combustion has three heat release stages: they are the cool flame reactions by long straight molecules such as n-heptane, the obstructed preignition by the formation of benzyl radical from aromatics such as toluene, and the main heat release stage [12].…”
Section: Effect Of Fuel Composition On Ignition Processsupporting
confidence: 87%
“…Machrafi and Cavadias [12]. found that the homogenous charge compression ignition combustion has three heat release stages: they are the cool flame reactions by long straight molecules such as n-heptane, the obstructed preignition by the formation of benzyl radical from aromatics such as toluene, and the main heat release stage [12]. The two heat release …”
Section: Effect Of Fuel Composition On Ignition Processmentioning
confidence: 98%
“…Considering these observations, the aim of this paper can be divided in two parts. The first is to validate experimentally the reduced kinetic mechanism against experimental concentration profiles with the use of an HCCI engine [20,21,42]. In this study, the experimental concentration profiles are extracted from [43] and reconverted from ppmC into ppmv.…”
Section: Introductionmentioning
confidence: 99%
“…For branched aromatics, however, the situation is different. For toluene for example, several researchers [51,52] reported that the toluene molecule reacts with OH to form the relatively stable benzyl radical and hereby acts as a sink for the OH radicals which in a pure alkanic fuel blend induce the second-stage ignition. Both these phenomena reduce the cool flame and overall reactivity and hence delay the second-stage ignition.…”
Section: Overall Reaction Schemementioning
confidence: 99%